2017
DOI: 10.1021/acssuschemeng.7b02613
|View full text |Cite
|
Sign up to set email alerts
|

Chiral 2-Aminobenzimidazoles in Deep Eutectic Mixtures: Recyclable Organocatalysts for the Enantioselective Michael Addition of 1,3-Dicarbonyl Compounds to β-Nitroalkenes

Abstract: A catalytic system based on deep eutectic solvents and chiral 2-amino benzimidazole organocatalysts is used to promote the enantioselective addition of 1,3-dicarbonyl compounds to β-nitrostyrenes. This procedure avoids the use of toxic VOC as reaction medium, providing access to highly functionalized chiral molecules in a selective and efficient manner. Furthermore, the reaction can be performed on a large scale and the recyclability of the catalytic system is possible at least for four times, leading to a cle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 52 publications
0
18
0
Order By: Relevance
“…As shown in Table 1, entries 12 and 13, under these conditions compound 4 was obtained with similar enantioselectivities with only a small erosion of the reaction conversion. For asymmetric organocatalyzed processes, the use of DES as a reaction medium has been barely studied, with the aldol reaction [30][31][32][33][34] and conjugated addition [13,29,35] being the main focus. For these processes a rational design of the organocatalyst and the right choice of the DES has shown to be critical to obtain good results and allow organocatalyst recycling.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As shown in Table 1, entries 12 and 13, under these conditions compound 4 was obtained with similar enantioselectivities with only a small erosion of the reaction conversion. For asymmetric organocatalyzed processes, the use of DES as a reaction medium has been barely studied, with the aldol reaction [30][31][32][33][34] and conjugated addition [13,29,35] being the main focus. For these processes a rational design of the organocatalyst and the right choice of the DES has shown to be critical to obtain good results and allow organocatalyst recycling.…”
Section: Resultsmentioning
confidence: 99%
“…Our research group has established the practicality of bifunctional chiral 2-aminobenzimidazole derivatives [20,21] 1 and 3 (Scheme 1) as efficient organocatalysts in the asymmetric conjugate addition of 1,3-dicarbonyl compounds to nitroolefins [22] and maleimides [23,24] as well as in the αfunctionalization [25][26][27][28] of these interesting nucleophiles using volatile organic solvents (VOCs) as a reaction medium. More fascinating, we have also demonstrated that the catalytic system based on the deep eutectic solvent choline chloride/glycerol and chiral 2-aminobenzimidazole organocatalysts 2 efficiently promotes the enantioselective addition of 1,3-dicarbonyl compounds to β-nitrostyrenes, avoiding the use of toxic VOC as reaction media [29].…”
Section: Introductionmentioning
confidence: 95%
“…Compared to the related ionic liquids (ILs), DESs are cheaper, easier to make, tunable, highly biodegradable, virtually non-toxic and do not require further purification. As illustrated by the exponential growth of literature, DES technology has been applied to a wide-ranging area of research topics such as organic synthesis, 31,32 metal-catalysis [33][34][35][36] and organocatalysis, [37][38][39][40] energy technology, 41,42 material chemistry, 43 or separation processes. 44 In biocatalysis, since the 2008 proof-of-concept, 45 many examples have showcased ad hoc protocols for biotransformations in DESs and DES-buffer mixtures.…”
Section: Figure 1 Examples Of Biaryl-containing Drugs: Valsartane (1mentioning
confidence: 99%
“…The use of DES as a reaction medium for asymmetric organocatalyzed processes has been barely studied being the aldol reaction [30][31][32][33][34] and conjugated additions [13,29,35] the main targets with the choice of the DES and design of the organocatalyst shown to be crucial to achieve good results and enable the organocatalyst recycling.…”
Section: Scheme 1 Chiral Benzimidazoles In Asymmetric Organocatalysismentioning
confidence: 99%
“…Our research group has demonstrated the practicality of bifunctional chiral 2aminobenzimidazole derivatives [20,21] 1 and 3 (Scheme 1) as efficient organocatalysts in the asymmetric conjugate addition of 1,3-dicarbonyl compounds to nitroolefins [22] and maleimides [23,24] as well as in the -functionalization [25][26][27][28] of these interesting nucleophiles using volatile organic solvents (VOCs) as reaction medium. More fascinating, we have also demonstrated that the catalytic system based on the deep eutectic solvent choline chloride/glycerol and chiral 2aminobenzimidazole organocatalysts 2 efficiently promotes the enantioselective addition of 1,3dicarbonyl compounds to β-nitrostyrenes, avoiding the use of toxic VOC as reaction medium [29].…”
Section: Introductionmentioning
confidence: 95%